Fibroblast growth factor receptor 1 protein (FGFR1) as potential prognostic and predictive marker in patients with luminal B breast cancers overexpressing human epidermal receptor 2 protein (HER2) - Belhadj Amina; Addou Klouche Lynda; Seddiki Sonia; Belhadj Adel; Benammar H Jelloul; Medjamia Miloud; Sahraoui Tewfik (Wolters Kluwer Medknow Publications, 2021)
Context: Breast cancer is the most common cause of cancer mortality among women worldwide. It is a heterogeneous disease partly responsible for treatment failure in luminal B patients. Deregulation of fibroblast growth factor signaling has been found and its therapeutic/prognostic value is explored. Aims: Most of the research has studied the FGFR1 gene while our study explored its protein expression by immunohistochemestry and examined the association with clinicopathological features, different molecular subtypes and survival. Subjects and Methods: Formalin-fixed and paraffin-embedded samples of invasive breast carcinomas were used to analyze FGFR1 expression. FGFR 1 was scored by percentage and intensity of cell cytoplasm staining, correlations were investigated and survival curves were constructed. Statistical Analysis Used: Chi-square test was used to assess the relationship between the marker expression and the clinicopathological characteristics. Overall specific survival curves were estimated using the Kaplan-Meier method and statistical significance was assessed using the log-rank test. Results: FGFR1 was associated at different staining threshold cut-offs with tumor size (P = 0.002), infiltrating lymph node (P = 0.022), distant metastasis (P = 0.003), positive estrogen receptor (P = 0.000), HER2 overexpression (P = 0.044) and luminal phenotypes (P = 0.026). The results also emphasize FGFR1 correlation expression with distant metastasis in luminal B tumors (P = 0.035) but not with luminal A and with overexpressed HER2 protein in both luminal tumors. FGFR1 expression affect luminal B patients survival with poor outcome. Conclusions: FGFR1 expression may serve as a prognostic and predictive factor in luminal breast cancers, it can also be considered as a potential therapeutic target in luminal B cases.